Clinical applicability of dOFM devices for dermal sampling. Issue 4 (13th April 2013) - Bodenlenz, M.; Aigner, B.; Dragatin, C.; Liebenberger, L.; Zahiragic, S.; Höfferer, C.; Birngruber, T.; Priedl, J.; Feichtner, F.; Schaupp, L.; Korsatko, S.; Ratzer, M.; et al.
<x xml:space="preserve">Abstract</x> Background Sampling the dermal interstitial fluid (ISF) allows the pharmacokinetics and pharmacodynamics of dermatological drugs to be studied directly at their site of action. Dermal open‐flow microperfusion (dOFM) is a recently developed technique that can provide minimally invasive, continuous, membrane‐free (thus unfiltered) access to the dermal ISF. Herein, we evaluate the clinical applicability and reliability of novel wearable dOFM devices in a clinical setting. Methods Physicians inserted 141 membrane‐free dOFM probes into the dermis of 17 healthy and psoriatic volunteers and sampled dermal ISF for 25 h by using wearable push‐pull pumps. The tolerability, applicability, reproducibility, and reliability of multiple insertions and 25 h continuous sampling was assessed by pain scoring, physician feedback, ultrasound probe depth measurements, and 25 h‐drift and variability of the sodium relative recovery. Results Insertion pain was moderate and decreased with each additional probe. Probe insertion was precise, although slightly deeper in lesional skin. The wearable push‐pull pump enabled uninterrupted ISF sampling over 25 h with low variability. The relative recovery was drift‐free and highly reproducible. Conclusion dOFM sampling devices are tolerable and reliable for prolonged continuous dermal sampling in a multiprobe clinical setting. These devices should enable the study of a wide range of drugs and their biomarkers in the skin.